Pediatric pulmonology in a developing country: our focus - Pekcan, Sevgi; Aslan, Ayşe Tana; Kiper, Nural; Köse, Mehmet; Cinel, Güzin; Cobanoğlu, Nazan; Yalçin, Ebru; Doğru, Deniz; Ozçelik, Uğur (The Turkish Journal of Pediatrics, 2011)
This study was designed to determine the profile of our pediatric pulmonology unit in Turkey, a developing country, by investigating the patients admitted to our unit for the first time. Our objectives were: to determine the profile of patients admitted for the first time, to compare their initial diagnoses before referral to our hospital with the diagnoses determined in our unit, to determine the definitive diagnoses for patients requiring advanced intervention with invasive diagnostic methods, and to follow the treatments, operations and invasive-noninvasive mechanical ventilation practices. With these objectives in mind, the records of 412 patients who visited the pediatric pulmonology clinic within a six-month period were reviewed. The referral diagnoses, consisting mostly of primary ciliary dyskinesia, recurrent lung infections caused by immune deficiency and bronchiectasis, as well as definitive diagnoses were recorded. Tuberculosis (14%), cystic fibrosis (7.8%), bronchiectasis (4.6%), immune deficiency (1.6%), hydatid cyst (2%), and primary ciliary dyskinesia (1%) were the most commonly diagnosed diseases. Final diagnosis in 145 of the 412 patients (35.2%) differed from the referral diagnosis. Consanguineous marriages are encountered more commonly in developing countries like Turkey, leading to an increased incidence of genetic diseases such as primary ciliary dysgenesis, cystic fibrosis and immune deficiencies. Infectious diseases such as hydatid cyst and tuberculosis are also common. In any country in which there is a unique distribution of diseases, in other words, a characteristic and unique disease spectrum, courses and instructional fellowship programs should be arranged accordingly.